Amelanotic Melanoma Treated as Fungal Infection for Years. (7th November 2022) - Kuceki, Guilherme; Deacon, Dekker C.; Secrest, Aaron M.
Abstract : This study describes a case of amelanotic lentigo maligna melanoma in a 69-year-old female that had been growing for approximately 5 years. The asymptomatic lesion had been previously diagnosed and treated as a fungal skin infection, an inflammatory rash, and an actinic keratosis that did not respond to standard treatments. Biopsy revealed confluent and nested atypical melanocytes at the dermal-epidermal junction, consistent with melanoma in situ. Excisional biopsy revealed invasive lentigo maligna melanoma, Breslow depth 0.3 mm, with positive melanoma in situ at margins. She is now 3 years post-Mohs surgery without recurrence. When working up a patient with a hypopigmented or inflammatory lesion not responding to standard therapies, physicians should always consider biopsy to rule out unusual neoplastic etiologies, such as amelanotic melanomas.